The dynamics of blood pressure within 12 months after carotid artery stenting in patients with stenotic carotid lesions - F. B. Shukurov; E. S. Bulgakova; A. N. Shapieva; B. А. Rudenko; T. V. Tvorogova; A. S. Shanoyan; A. Yu. Suvorov; D. A. Feshchenko; D. . S. Chigidinova; D. K. Vasiliev; A. V. Kontsevaya; O. M. Drapkina (Российский кардиологический журнал, 2019)
Aim. To assess the dynamics of blood pressure (BP) and determine the predictors of the hypotensive effect after carotid artery stenting (CAS).Material and methods. The analysis included 99 patients who underwent CAS in a period of March 2014 and May 2016. Inclusion criteria: (1) the presence of 50% symptomatic or 70% asymptomatic stenosis of the carotid artery (according to NASCET criteria), (2) follow-up for at least 1 year, (3) measurement and recording of BP at four points: 24 hours before surgery, 1 hour, 24 hours and 12 months after surgery. Results. According to office measurement of BP, the average systolic/diastolic pressure was 117,11/60,75, 119,73/60,75, 134,75/70,48 mm Hg after 1 hour, one day and 12 months after the intervention, respectively. In comparison with the average numbers of BP before the intervention, 148,13/89,52 mm Hg there was a significantly significant decrease in BP levels after CAS (p<0,01). According to the results of daily monitoring of blood pressure, a statistically important decrease in blood pressure was observed after 1 year of observation (p<0,01) (136,52/76,84 compared with 145,91/87,63 before the intervention). Dissociated circle of Willis (odds ratio=10,37, 95% confidence interval, from 3,64 to 29,52; p<0,001) and the occurrence of intraoperative hypotension (odds ratio =3,62, 95% confidence interval, from 1,16 to 11,28; p<0,027) were predictors of a persistent decrease in BP after CAS. Conclusion. The obtained results indicated the need for more thorough conservative postoperative management, especially for patients with a dissociated circle of Willis. It is also necessary to achieve the target blood pressure values by individualized correction of antihypertensive therapy.